The Influence of Graphic Design in Digital Marketing Industry: An Experimental Study - Muh Kholid Rizky Sapawi; Vici Tiara Anjarsari; Kristiawan Nugroho; Retnowati (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
Graphic design has become a key element in shaping consumer perception and influencing engagement metrics in digital marketing. This study aims to explore the role of graphic design in the success of digital marketing campaigns through an experimental approach. The study compared the performance of visually optimized content with non-optimized content on various digital platforms, including social media, websites, and email marketing. The results of the experiment showed that content with optimized graphic design resulted in significant increases in consumer engagement, brand recall, and conversion rates. The increase in consumer engagement reached an average of 35%, while brand recall increased by up to 20% compared to non-optimized content. This study highlights the importance of integrating design aesthetics into digital marketing strategies to achieve higher effectiveness. The findings provide practical insights for marketing professionals in designing more visually appealing campaigns, while opening up opportunities for further research on the specific elements of graphic design that have the greatest impact on consumer behavior. Thus, this study strengthens the strategic role of graphic design in the era of digital-based marketing.